The Challenge to change : reforming health care on the front line in the United States and the United Kingdom - Givan, Rebecca Kolins, 1975- (Culture and politics of health care work., 2016)
There is constant pressure on hospitals to improve health care delivery and increase cost effectiveness. New initiatives are the order of the day in the dramatically different health care systems of the United States and Great Britain. In this book, Rebecca Kolins Givan analyses the successes and failures of efforts to improve hospitals and explains what factors make it likely that the implementation of reforms will be rewarded by positive transformation in a particular institution's day-to-day operation.